Adapting pediatric obesity care to better suit adolescent patients: Design of a treatment platform and results compared with standard care in the national patient quality register - Annika Janson (Wiley, 2021)
Abstract Background Obesity constitutes a critical risk for adolescent health. This study aimed at identifying youth‐friendly components of obesity treatment. Methods In this feasibility study, an adolescent obesity treatment platform was implemented at two Pediatric outpatient clinics in Sweden. Body mass index (BMI), BMI z‐score, and the category of obesity (International Obesity Task Force) were compared before and after the intervention and with data on standard care from the Swedish Childhood Obesity Treatment Register. Results The study included 99 participants (49 females) aged 13–18 years from 1 September 2014, to 31 December 2016. A pediatric nurse met the participants on average 6.5 times in the average inclusion period of 15 months. Physical activity sessions attracted 63 participants. Acceptance Commitment Therapy and In Real Life groups attracted 24 participants. At inclusion, 62 participants had obesity and 37 severe obesity, and 71/99 (72%) remained in the same category. The mean BMI increased from 32.0 to 33.4 kg/m2 (p < 0.01), but 56/94 (60%) participants lowered their BMI or increased less than 1 kg/m2 and 73% stayed to the end of the study. Participants who were new to treatment and participants coming for more than eight visits to the nurse did not increase in BMI. BMI did not change for the 221 out of 641 register patients who had two recordings of BMI in the study period. Conclusions The platform was successful in increasing retention, and 60% of participants lowered or maintained their BMI. Still, seven out of ten adolescents with obesity or severe obesity remained in the same weight category.